华语语系哲学作为世界哲学：方法论刍议 *: Sinophone Philosophy as a Part of World Philosophy: A Preliminary Discussion - ISHII, Tsuyoshi (ERUDITE: Journal of Chinese Studies and Education, 2020)
本文倡议的“华语语系哲学”应该是一个比较陌生的概念。它既然与中国哲学区分开来，自有其不同的愿景。和其他的华语语系研究一样，它注重华语语系内部以及其边界各不相同的声音。华语语系哲学要以汉字书面语言系统为共性的基础，关照以声音为代表的每一个个体生命之单独性以及身体性。华语语系哲学不但要对跨文化的比较提供一个维度，更要对在互为他者的两个异乡人相邂逅时的伦理以及由此显现出来的真理加以特别的关注。为此，华语语系哲学把研究对象从中国哲学的范围扩张到广大华语语系世界，在着眼于华语语系随风而动、内外相交的流动性和他者性特点，联结不同的语言，并要避免单纯比较进而陷入相对主义。这样的哲学实践，应该并入世界哲学运动的一部分。日本学者近年来开始提倡创造世界哲学，呼吁要同等对待地球上不同地区的各种哲学，把哲学话语从古希腊以来的单一起源话语传统解放出来，从而改变我们对世界的认识方式以及哲学本身的话语方式。华语语系哲学要响应这个呼吁，在侧重流动性和转化性的基础上，从哲学的原生态出发要建立新的哲学话语。本文以公元9世纪日本的哲学家空海《声字实相义》为例，试图给未来开展的华语语系哲学运动提出一个方法论视角。 Abstract To date, the term “Sinophone philosophy” seems not so common. To say “Sinophone” instead of “Chinese”, indicates some unique prospect that would not be shared with Chinese philosophy. Much like other Sinophone studies, Sinophone philosophy considers the abundant differences between speech sounds emerging within the Sinophone sphere or on its periphery. It stands on a shared writing system –– Chinese characters, or kanji –– to embrace each individual voice that represents one’s physical existence. It aims not only at a trans-cultural comparison of regional philosophies, but it also engages with the ethics of trans-cultural encounters, in so far as it emerged from and remains embedded in a trans-cultural and trans-lingual context. In practical terms, Sinophone philosophy could be a part of the movement to engage with world philosophy, which has been advocated by some philosophers in Japan. They argue that in order to liberate philosophy from a Eurocentric view rooted in the ancient Greek tradition, contemporary philosophy should transform itself to provide an equal footing for different philosophical traditions in the world. By developing a world philosophy, they seek to transform our way of seeing the world. In this paper, I will argue that Sinophone philosophy can support the world philosophy movement, such that it could broaden its scope to reclaim individual philosophical endeavor in Jaspers’ sense of the term philosophizing. In particular, the paper considers a text written by Kūkai, the ninth-century Japanese philosopher and Buddhist monk, to indicate a possible methodology of Sinophone philosophy. Keywords: Sinophone philosophy, Chinese philosophy, world philosophy, Jaspers, Kūka